"Single‐cell pattern" of adenocarcinoma cells in effusion cytology: Morphologic challenges of lung cancer. Issue 1 (20th August 2020) - Guleria, Prerna; Barwad, Adarsh; Malik, Prabhat S.; Madan, Karan; Jain, Deepali
Abstract: Background: Lung adenocarcinomas present as tight clusters and three‐dimensional balls in effusion specimens. Unlike carcinomas of breast and stomach where singly lying malignant cells are seen in effusion samples, lung adenocarcinomas usually show cohesive morphology. This single‐cell pattern may also be confused with reactive mesothelial cells. We studied the frequency of pulmonary adenocarcinoma with single‐cell pattern cytomorphology in pleural effusion specimens. Materials and Methods: All cases reported as either suspicious or positive for malignancy on pleural effusion cytology (PFC) over the past 1 year were retrieved. The clinical details were obtained from requisition forms. Cases with predominant single‐cell pattern, clinically suspicious of carcinoma lung were segregated. These were de‐stained and immunocytochemistry (ICC) for TTF‐1 was performed. Results: Of 103 cases reported as either suspicious or positive for malignancy on PFC, 29 had a predominant single‐cell pattern. Of these, 13 (44.8%) were primary lung carcinoma. The rest were metastasis from ovary (5; 17.2%), breast (2; 6.9%), stomach (2; 6.9%), lymphoma (1; 3.5%), and Ewing's sarcoma (1; 3.5%). Five (17.2%) were those with unknown primary. All cases of lung carcinoma were positive for TTF‐1 ICC. Conclusion: Single‐cell pattern of pulmonary adenocarcinoma is commoner than popularly believed. This pattern may be difficult to differentiate from carcinoma cells of other sites as well as from reactive mesothelial cells. A high degree of suspicion is therefore needed to perform relevant ICC to clinch the correct diagnosis.